Pengaruh Kepemimpinan Kepala Cabang dan beban kerja Terhadap Kinerja Pegawai Perumda BPR Kuningan Dengan Motivasi Sebagai Variabel Moderasi - Yandi Wahyudi; Dikdik Harjadi; Odang Supriatna (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Competition between national, private banking institutions and banks with regional stocks has very tight competition. The empirical influence that we can see from this competition is the need for good performance due to a fairly high workload, so we can see that almost all banks always return home beyond the predetermined work limit, especially at the end of the month. The majority of Perumda BPR Kuningan employees aged 20-35 years are fresh graduates who still lack experience. Therefore, employee performance is still considered less than optimal, so that employee performance at Perumda BPR Kuningan is still not optimal. Data processing techniques using smartPLS. The results of this study are that the leadership of the Branch Head has a positive effect on employee performance, workload has a negative effect on employee performance, work motivation can moderate the influence of Branch Head Leadership on employee performance, work motivation can moderate the influence of Workload on employee performance.